Pharyngo-esophageal! diverticulum. Cricopharyngeal ntiotomy. Diverticulopexis. - Suiffet, Walter; Machado, Romeu; Liard, Washington; Soto Cordano, José; Vega, Dardo (Cirugía del Uruguay, 1976)
Problems derived from pharingo-esophageal diverticula have already been dlscussed in prevlous papers. In thls one an analysis is made of the evolution in surgical therapy, stressing the importance of the cricopharyngeus f1bers of the lower faringeal constrictor muscle as a pathogenical element to be solved surgically. Miotomy of cricopharingeus muscle is discussed, including a brief summary of bibliography and technique. Miotomy may be isolated, with diverticulectomy or diverticulopexis. Two cases of miotomy and diverticulopexis are reported. Results, a year or two after surgery, have been excellent. The technique for cricopharyngeal miotomy is simple. Diverticulopexis prevents the risk of complicated infections, fistula and stenosis. In those cases where surgical treatment is indicated results have proved excellent.